CERVICAL PRECANCER IN TERMS OF PERSISTENT HUMAN PAPILLOMAVIRUS INFECTION - Татьяна Владимировна Клинышкова; Мария Сергеевна Буян (The Publishing House Medicine and Enlightenment, 2018)
The aim of the research - to determine the features of cervical intraepithelial neoplasia (CIN) with persistent human papillomavirus infection. Materials and methods. This prospective study included 63 patients with CIN associated with HPV. Assessment of persistence of HPV was based on detection of HPV when retesting 12 months. Depending on the results allocated to 2 groups: 1A group (main, n = 26), including patients with CIN after treatment and persistence of HPV 32,0 years (26,25-39,00); 1B group (comparison, n = 37) - patients with CIN without HPV persistence after treatment 31,0 years (26,0-35,0). Results. In the beginning of the study two or more types of HPV HR was prevalent in patients of 1A group and were detected in 34.6 % of cases, against 16.2 % of cases among patients 1B group (p < 0.05). Two groups were dominated by HPV 16 (p > 0.05). After 12 months of treatment was 3.5-fold predominance of patients with mono-infection on HPV compared to co-infection of HPV (p < 0.05). Among patients with HPV-associated precancer recurrence with CIN II-III and absence of regression in CIN I were observed in 6 patients, made up 9.52 %, exclusively in 1A group, while in 1B group there was no recurrence (f = 3,92; p < 0.01). Conclusion. The features of the original infection status in patients with CIN on the background of persistent HPV infection. The recurrence of the disease in CIN II-III and the lack of regression of CIN I is marked when persistent for HPV infection that indicate risk of recurrence of cervical precancer after treatment in the absence of elimination of HPV.